Factors Influencing IPO Underpricing in Poland - Pomykalski, Przemysław; Filipiak, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
We review the theory and evidence on IPO activity and underpricing focusing on the Warsaw Stock Exchange. Although the topic has been under investigation in the past, we believe that the recent decade of low interest rates deserves inquiry. We research the extent of underpricing during this period and further conclude that three factors had a statistically significant influence on initial public offering underpricing during this period: the year of IPO, risk-free rate and WIG close value.